The Gastrointestinal Tract as a Key Target Organ for the Health-Promoting Effects of Dietary Proanthocyanidins - Cires, María José; Wong, Ximena; Carrasco-Pozo, Catalina; Gotteland, Martin (Frontiers in Nutrition, 2017)
Proanthocyanidins (PACs) are polymers of flavan-3-ols abundant in many vegetable foods and beverages widely consumed in the human diet. There is increasing evidence supporting the beneficial impact of dietary PACs in the prevention and nutritional management of non-communicable chronic diseases. It is considered that PACs with a degree of polymerization > 3 remain unabsorbed in the gastrointestinal tract and accumulate in the colonic lumen. Accordingly, the gastrointestinal tract may be considered as a key organ for the healthy-promoting effects of dietary PACs. PACs form non-specific complexes with salivary proteins in mouth, originating the sensation of astringency, and with dietary proteins, pancreatic enzymes and nutrient transporters in the intestinal lumen, decreasing the digestion and absorption of carbohydrates, proteins and lipids. They also exert anti-microbial activities, interfering with cariogenic or ulcerogenic pathogens in the mouth (Streptococcus mutans) and stomach (Helicobacter pylori), respectively. Through their anti-oxidant and anti-inflammatory properties, PACs decrease inflammatory processes in animal model of gastric and colonic inflammation. Interestingly, they exert prebiotic activities, stimulating the growth of Lactobacillus spp. and Bifidobacterium spp. as well as some butyrate-producing bacteria in the colon. Finally, PACs are also metabolized by the gut microbiota, producing metabolites, mainly aromatic acids and valerolactones, which accumulate in the colon and/or are absorbed into the bloodstream. Accordingly, these compounds could display biological activities on the colonic epithelium or in extra-intestinal tissues and, therefore, contribute to part of the beneficial effects of dietary PACs.